EXPRESSION OF mRNAS FOR CHEMOKINES AND CHEMOKINE RECEPTORS IN THE SKIN FROM PATIENTS WITH PSORIASIS - A. S. Beltiukova (SPb RAACI, 2014)
Abstract. Some issues in etiology and pathogenesis of psoriasis are poorly studied. Therefore, a search for new potential markers is actual for diagnostics of psoriasis in less clear cases. In this study, an attempt was undertaken to evaluate contribution of some chemokines and appropriate receptors into pathogenesis of psoriasis. The main group consisted of the patients with psoriatic arthritis (n = 20) and psoriasis vulgaris (n = 9). A group of comparison consisted of patients with sclerodermia (n = 4), and a control group was represented by healthy persons (n = 9). The specimens were taken from visually normal and affected skin areas from psoriatic patients obtained by punch biopsy. Expression of the following chemokines was performed: CCL3/MIP-1α, CCL4/MIP-1β, CCL5/RANTES, CCL11/eotaxin, CCL24/eotaxin-2, CXCL8/IL-8 and their receptors (CCR1, CCR3, CCR5, CXCR1, CXCR2). In cases with PASI values < 10, an increased expression of the following genes was revealed for CCL11/eotaxin (p = 0.03), CXCR1 (р = 0.008), CXCR2 (р = 0.0006) in virtually intact skin and affected skin areas, as well as increased gene expression of CCL24/eotaxin 2 (p = 0.009), CCL5/RANTES (p = 0.05) in visually normal skin.With PASI values of 10 to 20, an increased gene expression was found for CCL11/eotaxin (p = 0.005), CCL24/eotaxin 2 (p = 0.02), CCL5/RANTES (p = 0.01), CXCR1 (р = 0.0009), CXCR2 (р = 0.002) in skin biopsies from visually healthy and affected skin, as well as increased expression CXCL8 (IL-8) (p = 0.005) in visually normal skin. In cases with PASI > 20, an increased expression of CCL11/eotaxin (p = 0.001), CCL24/eotaxin 2 (p = 0.001), CCL3/MIP-1α (р = 0.02), CXCR1 (p = 0.0001), CXCR2 (p = 0.001) was detected in visually healthy skin samples and affected skin of the patients, as well as higher expression of CCL4/MIP-1β (р = 0.03) in affected skin areas. A reverse correlation was revealed between expression of chemokines, i.e., CCL24/eotaxin 2 (r = –0,94, p = 0.005), CCL3/MIP-1α (r = –0,94, p = 0.005), CCL4/MIP-1β (r = –0,85, p = 0.03) and their receptors: ССR5 (r = –0,79, p = 0.005) and CXCR2 (r = –0,94, p = 0.005) in visually normal skin of the patients with psoriasis and PASI values < 10.A direct correlation was found between expression of mRNAs for CCL11/eotaxin (r = 0.69, p = 0.04) in visually healthy skin from psoriatic patients, and CCR5 (r = 0.82, p = 0.006) in affected skin of the patients with psoriasis and PASI values of 10 to 20. In the group of patients with PASI values over 20, no correlations were detectable. These data allow us of concluding aboutan important contribution of chemokine system to pathogenesis of psoriasis. (Med. Immunol., vol. 10, N 4-5, pp 337-346).